Medical Tourism in Malaysia: Prospect and Challenges. - Abdullah Sarwar (Tehran University of Medical Sciences, 2013)
Tourism, combined with the phrase medical, seems to be a new form of tourism which has gained huge popularity in recent decades. Though, a number of literatures available with regard to the tourism industry and the competitiveness of the destination, however, the major aspects which determine the satisfaction of medical tourists are hardly focused specifically on Malaysia. There is a lack of empirical evidence in this area of study which needs to be bridged. Hence, this study aimed at investigating the various factors contributing towards the development of medical tourism in Malaysia.As the purpose of the research was to find out various factors contributing towards the development of medical tourism in Malaysia, so this study used Structural Equation modeling (SEM) for data analysis. The target population for this study consisted of the medical tourists coming to Malaysia with the primary intension of seeking medical procedures other than sightseeing. A total sample size of 266 was collected through non-probability judgment sampling during the period between December 2012 and February 2013.The result confirms that destination competitiveness and service quality play an important role in the medical tourist's mind towards medical tourism aspect in Malaysia. Thus, Malaysia need to promote various medical success stories together with the services they offer to attract more foreign patients.This study contributes to the theoretical development in the tourism industry by offering the structured relationship among various aspects contributing towards the development of medical tourism in Malaysia.